Clinicopathological characteristics of early gastric cancer associated with autoimmune gastritis. Issue 10 (16th September 2021) - Kitamura, Shinji; Muguruma, Naoki; Okamoto, Koichi; Kagemoto, Kaizo; Kida, Yoshifumi; Mitsui, Yasuhiro; Ueda, Hiroyuki; Kawaguchi, Tomoyuki; Miyamoto, Hiroshi; Sato, Yasushi; Aoki, Rika; Shunto, Joji; et al.
Abstract: Background: Autoimmune gastritis is known to be associated with neoplastic lesions but the relationship between autoimmunity and tumorigenesis have not been sufficiently clarified. The aim of this study is to assess the clinicopathological characteristics of gastric cancer cases associated with autoimmune gastritis. Methods: A total of 24 patients diagnosed as early gastric cancer with autoimmune gastritis were registered. Chart reviews with the data including age, gender, state of Helicobacter pylori infection, comorbidity, and concomitant gastric diseases were conducted. As for the characteristics of gastric cancer, location, size, morphological type, histopathology, invasion depth, and the presence of metachronous or simultaneous lesion were assessed. These data from autoimmune gastritis group were compared with those from 301 patients of early gastric cancer as a control group. Results: The gastric cancer associated with autoimmune gastritis was located in the upper, middle, and lower parts in 28.1%, 53.1%, and 18.8%, respectively. The morphological types are as follows: 0‐I, 9.4%; 0‐IIa, 28.1%; 0‐IIb, 15.6%; 0‐IIc, 46.9%; and 0‐III, 0.0%. The mean tumor size was 21.8 mm. While 90.6% were confined to the mucosa, 9.4% showed submucosal invasion. The histological classifications are as follows: tub1, 50.0%; tub2, 15.6%; pap, 21.9%; sig, 9.4%; and por, 3.1%. More numbers of female, protruded types, larger tumor size, papillary tumor, and that in the upper location were observed in autoimmune gastritis group compared to control group. Conclusion: Early gastric cancer associated with autoimmune gastritis demonstrated different characteristics from those without autoimmune gastritis including variety of tumor morphologies and histological types with female dominancy. Abstract : Autoimmune gastritis is known to be associated with neoplastic lesions but the relationship between autoimmunity and tumorigenesis have not been sufficiently clarified. This study assessed the clinicopathological characteristics of early gastric cancer cases associated with autoimmune gastritis. Early gastric cancer associated with autoimmune gastritis demonstrated different characteristics from those without autoimmune gastritis including variety of tumor morphologies and histological types.